Trade in mineral resources - Graham A. Davis (World Trade Organization (WTO), 2010)
This paper provides a review of current thinking on the economics of international trade in mineral resources. I first define what is meant by trade in mineral resources. I then discuss patterns of trade in mineral resources. The paper then moves on to the five topics requested by the World Trade Organization: theoretical and empirical literature on international trade in minerals; trade impacts of mineral abundance and the resource curse; the political economy of mineral trade in resource-abundant states; non-economic considerations associated with strategic mineral resources; and the impact of domestic market structure and regulation on production and trade in minerals.
Keywords: 330